Incorporation of solid wastes in red ceramics: an updated review - Vieira, C.M.F.; Monteiro, S.N. (Matéria, 2009)
A review on the fundamentals and technological advances in the incorporation of industrial solid wastes into red ceramics was updated since 1997, when the first overview on this subject was published by Dondi, Marsigli and Fabbri. Other works conducted before this period, but not covered by that overview were also reviewed. Modifications were introduced in the original categories of wastes to permit a wider variety to be considered. In addition to fuel and fluxing wastes, a category of property affecting wastes substituted the originally proposed fly-ash and plasticity reducing/ plastifying wastes categories. In order to be more comprehensive, this updated review considered industrially relevant subdivisions within each category. Accordingly, fuel wastes encompass: oily residues, blast furnace sludge, and paper industry residues. Fluxing wastes encompass: rejects from ornamental rocks, glassy residues and fluxing ashes. Property affecting wastes encompass: grog, water treatment sludge, steel-refining sludge/slag, non-fluxing ashes, mineral processing tails, galvanic sludge, spent catalyst reject, textile slurry, foundry reject sands, tannery sludge and construction and demolition leftovers.